2013
DOI: 10.5369/jsst.2013.22.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrical Properties of Indium Gallium Zinc Oxide Thin-Film Transistors by AZO/Ag/AZO Multilayer Electrode

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License(http://creativecommons.org/licenses/bync/3.0)which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Journal of Sensor Science and Technology Vol. 22, No. 2 (2013) AbstractWe fabricated an a-IGZO thin film transistor (TFT) with AZO/Ag/AZO transparent multilayer source/drain contacts by rf magnetron sputtering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…When silver is used instead, the conductivity at the top interface is lower, because silver typically does not oxidize in contact with IGZO (based on the Gibbs free energies of formation , ). Moreover, silver is reported to form a Schottky barrier with IGZO, which implies a high resistivity in the IGZO at this interface. , Therefore, under negative forming bias, a conductive filament based on oxygen vacancies growing from the bottom contact toward the top contact results in more stable switching events, as compared to the titanium top contact. Furthermore, the conductance in the pristine state under negative bias allows for the use of a lower CC during electroforming (see Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…When silver is used instead, the conductivity at the top interface is lower, because silver typically does not oxidize in contact with IGZO (based on the Gibbs free energies of formation , ). Moreover, silver is reported to form a Schottky barrier with IGZO, which implies a high resistivity in the IGZO at this interface. , Therefore, under negative forming bias, a conductive filament based on oxygen vacancies growing from the bottom contact toward the top contact results in more stable switching events, as compared to the titanium top contact. Furthermore, the conductance in the pristine state under negative bias allows for the use of a lower CC during electroforming (see Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the work functions of the single IZO layer and OMO multilayer were analyzed by using an UPS, which yielded 4.86 and 4.56 eV, respectively (details about photoelectron spectroscopy results are shown in Figure S3, Supporting Information). Therefore, it is concluded that the lower work function of the OMO multilayer compared to that of the single IZO electrode provides better contact with the n-type a-IGZO layer. , …”
Section: Resultsmentioning
confidence: 96%
“…Therefore, it is concluded that the lower work function of the OMO multilayer compared to that of the single IZO electrode provides better contact with the n-type a-IGZO layer. 32,33 Figure 3b shows the J−V curves of the p-Si NWs/n-IGZO LEDs. The current densities of the LEDs with all electrodes increased exponentially as the applied voltage increased under a forward bias.…”
Section: Resultsmentioning
confidence: 99%
“…c o m / l o c a t e / t s f deposition. This observation might shed light on a report of a Schottky contact feature based on Ag of~4.3 eV work function [20,21], which, according to Shimura's report [8], should make an Ohmic contact.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 83%